It's Not Just for Medical Professionals: Patient Resources of the National Comprehensive Cancer Network (NCCN). Issue 1 (2nd January 2023) - Phillips, Kat
Abstract: Patients and caregivers of patients with cancer are met with an untold amount of information resources, not all of which are ethical, accurate, healthy, or are simply motivated by profit or agenda. One way information professionals and health care providers can help sift through this overwhelming amount of resources is to provide credible and accessible cancer resources founded in evidence-based research and medicine. One such organization is the National Comprehensive Cancer Network, and their collection of Patient Resources.